Pengaruh Disiplin Kerja, Motivasi Kerja dan Komitmen Organisasi terhadap Kinerja Pegawai Dinas Pekerjaan Umum dan Penataan Ruang Kabupaten Barru - Haedar Dahing; Mashur Razak; Muhammad Hidayat (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2020)
This research aims to determine and analyze (1) the effect of work discipline, work motivation, and organizational commitment partially and simultaneously toward the employee performance at the Public Works and Spatial Planning Office in Barru (2) the most dominant variable affects employee performance. This type of research is descriptive quantitative with descriptive explanatory research. The research took place at the Public Works and Spatial Planning Office in Barru for 3 months. The population in this research was 81 employees at the Public Works and Spatial Planning Office in Barru. The sample is the entire population taken as a sample. Thus the number of samples is equal to the total population (census or saturated sample) so that a sample of 81 employees at the Public Works and Spatial Planning Office. The data analysis method used was a multiple linear regression model. The results show that (1) work discipline, work motivation, and organizational commitment partially and simultaneously affect the employee performance at the Public Works and Spatial Planning Office in Barru (2) work discipline is the most dominant variable that affects employee performance.